Phase Transformations of Siderite in Different Atmospheres - Mössbauer Spectroscopy Study - M. Kądziołka-Gaweł; Z. Adamczyk; M. Wojtyniak; J. Klimontko; J. Nowak (Archives of Foundry Engineering)
The decomposition process of siderite (FeCO3) heated in an oxygen atmosphere and in a vacuum up to a temperature of 700oC, and the identification of the products of this process was studied using the 57Fe Mössbauer spectroscopy method. Two siderite samples were used for investigations. The measurements showed that one of the siderites was pure FeCO3, and the other had significant amounts of magnesium (Fe,Mg)CO3. The research results indicate that the siderite decomposition process begins at a temperature of 300oC. The main products of siderite decomposition are Fe-oxide nanoparticles. The crystallization process of these Fe-oxide begins at temperatures at which the decomposition of siderite almost ends, i.e., around 400oC for FeCO3 and 500oC for (Fe,Mg)CO3. The final products of siderite decomposition are hematite and magnetite or magnesioferrite. The magnetite formed in this process is poorly crystalline, what is confirmed by X-ray diffraction measurements and the shape of the Mössbauer spectra.